(3TQM eQGM GdCQhGMs - (3OjcbhR, TeS GdOjf, CMeO OjcbhR TeS GdOjf, J HYO (B855(3g`s ((3eMeO Hf CMeOs)
(3ChdgG (B:s
(3Gddge jG eUQa GdbdhH UQa bdhHfG bGd GdeU QMeI Gddg Ydjg YedG HGdMOjK GdeTghQ hGdNHQ GdeCKhQ hGbJOGA HGdcJGH GdcQje HSe Gddg GdQMef GdQMje hJNUjU cJGHg HChd GdbQjfjf Hd PcQg ef HGH GdGcJaGA cbhdg JYGdis
(3BNQgG (B:s
(3Whi aEfg dh CYd GdhGh ajgeG HbdHg CdaG hHEScGfgG dKbd GdcSQI YdjgG de jdRe GLJeGY GdEYdGdjf EdG Cfg dG jYd MedG Ydi Whis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 138s
(3cTa GdXfhf(B: 2 / 1651s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas